PTH-146 Validation of direct observation of procedural skills (DOPS) assessments for paediatric colonoscopy. (8th June 2018) - Siau, Keith; Levi, Rachel; Howarth, Lucy; Broughton, Raphael; Tzvinokos, Christos; Feeney, Mark; Narula, Priya
Abstract : Introduction: Direct observation of procedural skills (DOPS) are tools designed by the Joint Advisory Group (JAG) to assess competence in endoscopy. These were expanded in July 2016 (new DOPS) to include those specific to paediatric colonoscopy. However, paediatric colonoscopy DOPS assessments have not been validated. We aimed to correlate overall trainee competence with components of the paediatric colonoscopy DOPS. Subjects and Methods: We performed a prospective UK-wide analysis of formative paediatric colonoscopy DOPS submitted to the JETS e-Portfolio over one-year (August 2016–2017). Scores were averaged across procedural domains (pre-procedural, procedural, post-procedural and endoscopic non-technical skills – ENTS). Each DOPS item, except for ENTS, were grouped into cognitive and technical skillsets by two independent investigators, and correlated with the overall performance score. Correlation analyses were performed using Spearman's test (rho >0.70 indicating high positive correlation). Results: 61 DOPS assessments were completed by 13 unique trainers for 14 trainees. Overall performance score comprised: 1: Maximal supervision (1.6%), 2: Significant supervision (13.1%), 3: Minimal supervision (47.5%) and 4: Competent (37.7%). By domain, overall competence correlated most with scores for the 'Procedural' domain (rho: 0.849, p<0.001), ENTS (0.666, p<0.001), 'Post-procedural' (rho 0.635, p<0.001) and pre-procedural (rho 0.471, p<0.001). By domain, overall score correlated more with performance in predominantly 'Cognitive' (rho 0.834, p<0.001) and 'Technical' (rho 0.815, p<0.001) domains compared to ENTS. In terms of DOPS items, overall competence score correlated most with 'Proactive Problem Solving' (rho 0.836, p<0.001) and 'Patient Comfort' (rho 0.826, p<0.001), and weakest with 'Confirms Consent' (rho 0.228, p=0.115) and 'Equipment Check' (rho 0.302, p=0.020). Conclusion: Competencies in paediatric colonoscopy, as assessed within DOPS, vary in their correlation with overall competence. Performance in the 'Procedural' domain, Proactive Problem Solving' items, and 'Cognitive' skillsets had greatest correlation with overall procedural competence. As assessors are completing the new DOPS in a consistent manner, this provides novel validity evidence for the new paediatric colonoscopy DOPS.